THE IMPACT OF GOVERNMENT SPENDING, FINANCIAL DEEPENING, AND UNEMPLOYMENT ON POVERTY REDUCTION IN INDONESIA - Jahrizal, Jahrizal; Rineliana; Rabani, Sultan Taqi Al; Andini, Nunung (Riau International Conference on Economics, Business and Accounting, 2024)
Poverty is viewed as the inability of a population from an economic perspective to meet basic food and non-food needs measured through expenditures. A person is considered poor if their per capita monthly expenditure falls below the poverty line (Central Statistics Agency, 2021). Based on the 2020 BPS publication, the percentage of poor people in Indonesia in 2020 was 10.19%, meaning that out of 34 provinces, only 19 had poverty rates below the national average, while the rest exceeded it. Nurkse (1952) introduced the theory of the vicious circle, where market imperfections lead to low productivity. Low productivity reduces people’s income, resulting in decreased savings and investments. This reduction in investment affects capital, leading to market imperfections, underdevelopment, and poverty, creating a continuous cycle of poverty. Government spending can be a solution to reduce poverty because, if done productively, it can stimulate economic activities in a region. One of the government’s roles is government spending, which serves as an economic activity regulator. According to Keynes, government spending can increase output and reduce the reaction rate because government spending can create jobs and boost people’s income, thus improving the welfare of society (Rahmawati, 2022). Government spending is the most effective government intervention in the economy, as it can increase production capacity, build infrastructure that employs labor, distribute income, and enhance the population’s well-being. All government spending is expected to have a positive impact on the economy. Government spending on education and health significantly and negatively affects poverty in East Lombok (Lantu, 2017). Yusri (2022) also found that government spending on education and health significantly affects poverty in Indonesia. Lantu et al. (2017) found that direct and indirect spending do not significantly affect poverty. Good financial deepening in a region is indicated by a high credit-to-gross Regional Domestic Product (GRDP) ratio. This implies that the region manages its finances well, and the higher the financial deepening ratio, the lower the poverty rate. This is in line with the results of Rewilak’s study (2017), which showed that financial deepening in the long run can reduce poverty. However, according to Harisuddin Hartono (2019), deep financial markets do not have a significant impact on poverty. The welfare of a region’s population can be reflected in the unemployment rate. Open unemployment has a significant positive effect on poverty (Futunanembun et al., 2023). Hasan et al. (2020) also stated that the open unemployment rate has a significant positive effect. This is in contrast to the study by Damayani and Perdini (2022), which found that open unemployment does not have a significant impact on poverty in Indonesian provinces. Based on the explanations above, it is known that there are varying responses among these variables in the relevant field, indicating that government spending, financial deepening, and unemployment can reduce the poverty rate. Therefore, further study and updates are needed to fill the research gap with new objects in the provinces of Indonesia. Can government spending, financial deepening, and unemployment be beneficial in poverty alleviation in Indonesia?